Análise de investimento da construção de conjuntos habitacionais: estudo de caso aplicado a construção de casas populares no Município de Itaitinga-Ce - Mesquita, Samuel Felix de (2021)
Among the most representative of the national Gross Domestic Product, the construction industry experienced a moment of recovery in 2019, muffled by the emergence of COVID-19, but with projections of recovery from the year 2021, when necessary to be resumed. to the construction works supported by the Housing Program Minha Casa, Minha Vida, among many other housing demands, because, according to the Brazilian Chamber of the Construction Industry, the Brazilian interest in the acquisition of real estate remains high with the search for The improvement of their quality of life, with an expected growth of around 4% of GDP and a better performance in relation to the other segments of the economy, since the Federal Government has a forecast of growth of the sector of around 2.8%, but with the concern of increasing and depleting some inputs in the sector, due to the pandemic. In the State of Ceará, it is realized that the civil construction segment is a leader in job creation, apparently, tending to growth and recovery, which led us to ask: The real estate projects produced and launched in the State are viable economically and economically. financially? To answer this question, using a descriptive methodology, a project located in the municipality of Itaitinga was chosen and this objective was achieved: the survey of the necessary data for the acquisition of inputs to carry out the project and the forecast of proceeds from the sale of 10 popular houses, using some investment analysis techniques, indicated their economic and financial viability, having obtained the following results: NPV of R $ 96,074.24, IRR of 52%, Payback of 4.4 years and 12-month time-to-market. Positive and expected indicators within the parameters used by capital market operators and economic and financial analysts at organizational institutions. It is believed that this work tends to add value in the design and application of financial management instruments, necessary to assess the economic and financial viability of any projects planned by small and medium-sized companies, in the civil construction segment, in the State of Ceará.